Crenarchaeota in Lake Michigan sediment. - MacGregor, B J (1997)
RNA from Lake Michigan sediment was hybridized with a DNA probe for archaeal 16S rRNA. There was a peak of archaeal rRNA abundance in the oxic zone and another immediately below it. Six contributing species were identified by PCR amplification of extracted DNA with primers specific for archaeal rDNA: two related to Methanosarcina acetivorans and four related to marine crenarchaeotal sequences. rRNA quantification using a DNA probe specific for this crenarchaeotal assemblage showed it is most abundant in the oxic zone, where it accounts for about 10% of total archaeal rRNA.